THE USE OF SIMPLE PAST TENSE IN RECOUT TEXT: (AN ERROR ANALYSIS) - Andra Dimaputri, Stephanie; Widyahening, Ch.Evy Tri (ENGLISH RESEARCH JOURNAL, 2025)
The research objectives were: 1) To find out the kinds of errors made by the tenth grade Students of SMK Kristen 2 Surakarta on using simple past tense in recount text. 2)To determine the dominant errors made by tenth grade Students of SMK Kristen 2 Surakarta on using simple past tense in recount text. The research subject was in class X TO (Teknik Otomotif), with 28 students. The method of data was qualitative research. This research was studied from the perspective of error analysis. There were omissions, additions, misinformation, and misordering in error analysis. The instruments used to collect the data were observation, interview, test, and documentation. After analyzing the data, the researcher found the total number of errors made by students and the total number of errors in percentage. There were Omission 20 (20%), Misinformation 77 (77%) and Misordering 3 (3%). So, the dominant error made by students was misinformation  In this research result, the cause of misinformation was that the students were still confused about the correct use of the structure had limited vocabulary, especially in irregular verbs and used the nominal verb in simple past tense. Keywords: Error Analysis, Recount Text, Simple Past Tense